The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.32607/actanaturae.10647
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the TGFB1 Gene to Myocardial Infarction Susceptibility

Abstract: Carriage frequencies of alleles and genotypes of the TGFB1 gene polymorphous loci -509C>T (rs1800469), 869T>C (rs1982073), 915G>C (rs1800471), which affect the level of cytokine TGF-β1 production, were analyzed in the patients of Russian ethnic descent with myocardial infarction (MI) (406 cases) and in the control group of the same ethnic descent (198 controls). Significant association with MI was observed in carriage frequencies of the allele TGFB1*-509T (p=0.046, OR =1.45, 95% CI: 1.02-2.06), genotypes TGFB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…The frequencies of SNPs rs1800469, rs1800470, and rs1800471 in healthy individuals identified in our study are consistent with the data of other domestic authors [ 17 , 18 ]. A comparison of the distribution of the allele frequencies studied in our work with the data deposited into the U.S. National Center for Biotechnology Information (NCBI) also did not reveal significant differences from that of Tgfb1 in the European population: rs1800469 – A(37%)/G(63%); rs1800470 – A(56%)/G(44%); and rs1800471 – C(94%)/G(6%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The frequencies of SNPs rs1800469, rs1800470, and rs1800471 in healthy individuals identified in our study are consistent with the data of other domestic authors [ 17 , 18 ]. A comparison of the distribution of the allele frequencies studied in our work with the data deposited into the U.S. National Center for Biotechnology Information (NCBI) also did not reveal significant differences from that of Tgfb1 in the European population: rs1800469 – A(37%)/G(63%); rs1800470 – A(56%)/G(44%); and rs1800471 – C(94%)/G(6%).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of the three most common haplotypes did not vary significantly between patients and healthy individuals. The analysis of the same Tgfb1 haplotypes conducted by other authors showed a similar prevalence of the most common haplotype, G-A-C, in healthy individuals, which was about 50–60% [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 73%
“…Цитокин TФРβ1 кодируется геном TФРβ1 (OMIM 190180), который расположен на длинном плече 19-й хромосомы в локусе 19q13.2 и состоит из 7 экзонов, разделенных 6 интронами. В настоящее время установлен ряд важных полиморфизмов -rs1800469, rs1800470, rs1800471, rs1800473 [33]. Полиморфизм rs1800469 локализован в промотерной области гена, Т-вариант полиморфизма приводит к повышению концентрации TФРβ1.…”
Section: на следующую на первую на предыдущую к содержаниюunclassified